Harvesting microalgal biomass using crossflow membrane filtration: critical flux, filtration performance, and fouling characterization. Issue 12 (18th June 2017) - Elcik, Harun; Cakmakci, Mehmet
ABSTRACT: The purpose of this study was to investigate the efficient harvesting of microalgal biomass through crossflow membrane filtration. The microalgal biomass harvesting experiments were performed using one microfiltration membrane (pore size: 0.2 µm, made from polyvinylidene fluoride) and three ultrafiltration membranes (molecular weight cut-off: 150, 50, and 30 kDa, made from polyethersulfone, hydrophilic polyethersulfone, and regenerated cellulose, respectively). Initially, to minimize membrane fouling caused by microalgal cells, experiments with the objective of determining the critical flux were performed. Based on the critical flux calculations, the best performing membrane was confirmed to be the UH050 membrane, produced from hydrophilic polyethersulfone material. Furthermore, we also evaluated the effect of transmembrane pressure (TMP) and crossflow velocity (CFV) on filtration flux. It was observed that membrane fouling was affected not only by the membrane characteristics, but also by the TMP and CFV. In all the membranes, it was observed that increasing CFV was associated with increasing filtration flux, independent of the TMP.